Kajian Lanskap Budaya Permukiman Adat Kampung Naga: Indonesia - Priyoga, Iwan; Nurkukuh, Dwi Kunto (REKA RUANG, 2024)
Kampung Naga is a traditional residential area that until now still adheres to the ancestral heritage. The harmony of life with nature gave birth to local wisdom that formed the Kampung Naga settlement to blend with nature. The cultural landscape of the Kampung Naga settlement illustrates the interaction of humans with nature which is formed in the patterns of space and buildings they inhabit. This research was conducted to determine the harmony of the concept of cultural landscape in the realization of the settlement pattern of Kampung Naga, as a manifestation of the balance of humans with the natural surroundings. The research was conducted using a qualitative descriptive method in the form of observation, interviews, and documentation. The analysis was carried out by comparing the variables of the saujana concept to the settlement pattern of Kampung Naga, which is related to its physical, territorial, and cultural arrangement.